INCREASING EDUCATIONAL ACTIVITY IN CHEMISTRY LESSONS - Umarov, Saidanvar; Sirojov, Farhod (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
In order to form a clear and deep understanding of the environment among secondary school students, a modern way of scientific thinking is needed, in which feedback is reflected both informative with the system and a professional approach to knowledge and education. The use of these methods stimulates the desire of students to complete tasks on their own, is characterized by an arbitrary concentration of attention on tasks, and there are fewer distractions in classes.